FORMATION OF ALL PRE-THORACIC VERTEBRAE AND ASSOCIATED TISSUES IN ANAMNIOTES AND AMNIOTES - PRABHU JEE (International Journal of Multidisciplinary Research and Studies, 2020)
The structure of the skull, the number of apertures in the skull, the presence of particular bones in the skull, and the structure of the limbs are some of the morphological and molecular criteria that are used in the categorization of amniotes. The sauropsids and the synapsids are the two most important subdivisions of the amniotes. To have a complete knowledge of the variety of vertebrate life on Earth as well as its history, it is vital to have a firm grasp on the taxonomy and development of amniotes. Both the bottlenose dolphin and the African elephant have been subjected to comparative anatomical research, which has found both similarities and differences between the two species. For instance, people of both species have hearts that are divided into four chambers and are warm-blooded, sometimes known as endothermic. Nonetheless, as a result of their adaptations to their respective surroundings, their skeletal structures are strikingly unlike one another. While the large and sturdy skull of the elephant is able to carry the weight of its enormous tusks, the delicate and streamlined skull of the dolphin reduces the amount of resistance it experiences when swimming. In a similar fashion, the teeth of an elephant are built for crushing tough plants, but the teeth of a dolphin are adapted for capturing and holding onto prey